When parents are incarcerated : interdisciplinary research and interventions to support children - Wildeman, Christopher James, 1979-; Haskins, Anna R.; Poehlmann-Tynan, Julie (Bronfenbrenner series on the ecology of human development., 2018)
"In the United States today, roughly 1 in 25 children has a parent behind bars. This insightful volume provides an authoritative, multidisciplinary analysis of how parental incarceration affects children and what can be done to help them. Contributors to this book bring a wide array of tools for studying the children of incarcerated adults. Sociologists and demographers apply sophisticated techniques for conducting descriptive and causal analyses, with a strong focus on social inequality. Developmental psychologists and family scientists explore how proximal processes, such as parent₆child relationships and micro-level family interactions, may mediate or moderate the consequences of parental incarceration. Criminologists offer important insights into the consequences of parental criminality and incarceration. And practitioners who design and evaluate interventions review a variety of programs targeting parents, children, the criminal justice system, and the plight of poor children more broadly. Given the vast implications of mass incarceration for individual children and their families, as well as the future of inequality in the United States, this book will serve as a definitive resource for researchers, practitioners, and policymakers.-- Preface. (PsycINFO Database Record (c) 2017 APA, all rights reserved)